2018
DOI: 10.1089/hs.2017.0064
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Potential Provider and Environmental Contamination on a Clinical Biocontainment Unit Using Aerosolized Pathogen Simulants

Abstract: The Johns Hopkins Hospital created a biocontainment unit (BCU) to care for patients with highly infectious diseases while assuring healthcare worker safety. Research to date for BCU protocols and practices are based on case reports and lessons learned from patient care and exercises. This study seeks to be the first to explore the influences of healthcare worker movement and personal protective equipment (PPE) doffing on the transport of simulant pathogen particles in a BCU. A cough device released 1 μm fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…This could provide safety data to better understand the potential advantages of PPE B compared with PPE A. 14 PPE A was tested first at both sites. The lack of randomization of PPE order in the study protocol may have introduced unintended biases toward one of the PPE ensembles.…”
Section: Discussionmentioning
confidence: 99%
“…This could provide safety data to better understand the potential advantages of PPE B compared with PPE A. 14 PPE A was tested first at both sites. The lack of randomization of PPE order in the study protocol may have introduced unintended biases toward one of the PPE ensembles.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the potential for HCW exposure to airborne pathogens is of concern in the doffing room due to multiple potential scenarios for this contamination. Thus far, between the present study and Drewry et al, these identified scenarios include HVAC exhaust failure, re‐aerosolization of particles deposited on the outside of HCW's PPE during doffing, and/or particle transport from the patient room after opening the door between the two spaces.…”
Section: Resultsmentioning
confidence: 77%
“…Drewry et al also noted the presence of simulant pathogen particles in the JH‐BCU doffing room following simulated patient care and doffing procedures. The key difference between the present study and the study of Drewry et al is that there were no HCWs in the present study; that is, particle dissemination was observed as a result of airflow patterns alone while manipulating HVAC condition. Therefore, the potential for HCW exposure to airborne pathogens is of concern in the doffing room due to multiple potential scenarios for this contamination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Of particular relevance to the current COVID-19 pandemic, the BCU team, in collaboration with the JH Applied Physics Lab, used a novel fluorescent microbead system to simulate the movement of infectious particles through a biocontainment environment and to assess the impact of environmental control systems and patient care protocols on the movement of these infectious simulants. 16,17 In partnership with HEIC, the BCU team combined these infectious simulants with more traditional methods to enhance the detection of selfcontamination during the doffing process, and to validate the use of a trained observer in the doffing process for viral hemorrhagic fevers. 18,19 The BCU team partnered with the JH Berman Bioethics Institute to explore the ethical, legal, and social implications of genomic research on containment care.…”
Section: Research and Innovation Prior To Covid-19mentioning
confidence: 99%